Accuracy of AF burden detection with the new Confirm Rx with Sharp-sense technology. (19th May 2022) - Briosa E Gala, A; Pope, MTP; Leo, M; Ormerod, J; Field, D; Balasubramaniam, R; Thomas, H; Gardner, RS; Hunter, R; Gallagher, MM; Wilson, D; Paisey, JR; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Implantable cardiac monitors (ICMs) are increasingly used to monitor atrial fibrillation (AF) burden following catheter ablation. AF burden recorded by the Confirm Rx™ ICM cannot be modified even after adjudication of false-positive (FP) episodes. We sought to investigate accuracy of the AF burden detection in a UK cohort. Methods: This multicentre retrospective study included patients with Confirm Rx™ and at least one episode >6 minutes across 9 UK hospitals. Each episode had a corresponding 120-second EGM (electrogram) and heart rate scatterplot which was considered representative of the whole episode. One cardiologist adjudicated all EGMs as 'True AF' or 'False positive' and a random sample of 10% was reviewed to account for intra and interobserver variability. AF burden was computed as the duration of all episodes classified as AF by the Confirm-Rx divided by the total duration of follow-up. 'True-AF' burden was calculated by dividing the duration of episodes adjudicated as 'True-AF' by the total duration of follow-up. We also investigated the accuracy of AF burden according to implantation indication and episode duration. Results: A total of 16, 230 individual AF episodes were included from 232 consecutive patients. Overall, 26, 137 hours of AF were recorded and a total follow-up 315 patient-years which equates to an AF burden of 0.95%. However, only 24, 404.7 (93.3%) hours represented time in 'True-AF' and a 'True-AF' burden for the whole cohort of 0.89% (Table 1). Patients with a Confirm-Rx™ for palpitations and suspected AF had the lowest proportion of 'True-AF' burden and had a modest contribution to the overall AF burden (Figure 1). Conversely, patients with known AF had the highest proportion of 'True-AF' burden recorded. Most AF (84.5%) episodes lasted less than 1 hour with approximately a quarter adjudicated as false-positive detections, but their contribution towards overall AF burden was very small (Figure 2A-2B). In contrast, AF >3 hours accounted for 76.4% of time in AF and the proportion of 'True-AF' burden was 98.5%. Conclusion: The accuracy of the estimated AF burden for the whole cohort was excellent (93.3%), driven by the high proportion of 'True-AF' burden in AF>3 hours.